2003
DOI: 10.1521/aeap.15.1.1.23845
|View full text |Cite
|
Sign up to set email alerts
|

Skills Training versus Health Education to Prevent STDs/HIV in Heterosexual Women: A Randomized Controlled Trial Utilizing Biological Outcomes

Abstract: We compared the effectiveness of two different 16-session group interventions for reducing new STD infection among heterosexual women. Two hundred twenty-nine at-risk heterosexual women were randomly assigned to skills training (ST) based on the relapse prevention model or health education (HE). Participants were monitored during the year following intervention for STD acquisition, self-reports of sexual behavior, and risk reduction skills. Participants in the ST intervention were significantly less likely to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Gender-specific skills training holds out promise as such a prophylaxis. Whether it takes place in school or out of school, training should go beyond general health education to combine knowledge of HIV prevention with skills for negotiating safe sexual behaviour that are sensitive to the local social context (Baker et al, 2003;Exner et al, 1997). This might take the form of peer educators in rural communities who impart relevant and accurate HIV/AIDS knowledge in after-school programmes, or it might consist of teachers and other professionals engaging young women in problem-solving, relational skill-building, and role-playing activities that are tailored to fit the realities of their lives (Agha, 2002;Albarracín et al, 2003;Miller et al, 2000;Perez & Dabis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Gender-specific skills training holds out promise as such a prophylaxis. Whether it takes place in school or out of school, training should go beyond general health education to combine knowledge of HIV prevention with skills for negotiating safe sexual behaviour that are sensitive to the local social context (Baker et al, 2003;Exner et al, 1997). This might take the form of peer educators in rural communities who impart relevant and accurate HIV/AIDS knowledge in after-school programmes, or it might consist of teachers and other professionals engaging young women in problem-solving, relational skill-building, and role-playing activities that are tailored to fit the realities of their lives (Agha, 2002;Albarracín et al, 2003;Miller et al, 2000;Perez & Dabis, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of intervention condition and number of sessions attended was examined in three ways: with Repeated Measures ANOVA to test whether these factors affected within-trajectory group change; Chi Square to test whether intervention condition was associated with trajectory membership; and ANOVA to test whether trajectory groups differed in number of sessions attended. (See Baker et al, 2003 for other outcome analyses for this study). ANOVA and Chi-square were used to examine other pre-intervention differences between the growth trajectory groups.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 8 interventions focused exclusively on women or adolescent females, 46,48,[50][51][52]59,[65][66][67][68][69][70][71][72] and another intervention targeted women in relationships while including their male partners in the study sample (i.e., 50% women). [53][54][55] Of the 9 interventions for women, 8 included mostly minority women (range, 58%-100%).…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Nine of the 10 reporting unemployment status consisted of mostly unemployed participants. 46,47,[53][54][55]59,62,[67][68][69][70][71][72][73][74] An additional 4 studies provided information regarding income or public housing that indicated participants were of low socioeconomic status. [50][51][52]60,61,65,66,75,76 Intervention Characteristics All best-evidence interventions relied on at least 1 behavioral change theory or model, with the most common being Social Cognitive Theory (n = 7), Social Learning Theory (n = 4), AIDS Risk Reduction Model (n = 3), Information-Motivation-Behavior Model (n = 3), and the Theory of Gender and Power (n = 3) (not mutually exclusive).…”
Section: Population Characteristicsmentioning
confidence: 99%